Myeloid lineage cells evince distinct steady-state level of certain gene groups in dependence on hereditary angioedema severity - Ballonová, Lucie; Souček, Přemysl; Slanina, Peter; Réblová, Kamila; Zapletal, Ondřej; Vlková, Marcela; Hakl, Roman; Bíly, Viktor; Grombiříková, Hana; Svobodová, Eliška; Kulíšková, Petra; Štíchová, Julie; et al. (Frontiers in Genetics, 2023)
Hereditary angioedema (HAE) is a rare genetic disorder with variable expressivity even in carriers of the same underlying genetic defect, suggesting other genetic and epigenetic factors participate in modifying HAE severity. Recent knowledge indicates the role of immune cells in several aspects of HAE pathogenesis, which makes monocytes and macrophages candidates to mediate these effects. Here we combined a search for HAE phenotype modifying gene variants with the characterization of selected genes’ mRNA levels in monocyte and macrophages in a symptom-free period. While no such gene variant was found to be associated with a more severe or milder disease, patients revealed a higher number of dysregulated genes and their expression profile was significantly altered, which was typically manifested by changes in individual gene expression or by strengthened or weakened relations in mutually co-expressed gene groups, depending on HAE severity. SERPING1 showed decreased expression in HAE-C1INH patients, but this effect was significant only in patients carrying mutations supposedly activating nonsense-mediated decay. Pro-inflammatory CXC chemokine superfamily members CXCL8, 10 and 11 were downregulated, while other genes such as FCGR1A, or long non-coding RNA NEAT1 were upregulated in patients. Co-expression within some gene groups (such as an NF-kappaB function related group) was strengthened in patients with a severe and/or mild course compared to controls. All these findings show that transcript levels in myeloid cells achieve different activation or depression levels in HAE-C1INH patients than in healthy controls and/or based on disease severity and could participate in determining the HAE phenotype.